The single phase railway - Coldwell, William Irving (My University, 1906)
Introduction: It was not until recent years that the single phase alternating current motor assumed much importance and only very recently that it was found to possess a certain adaptability to traction; on account of the simplicity of the design and the great amount of speed regulation that one can obtain. With the rapid development of the applications of electricity, alternating current motors were required for railway and similar work which had a high-starting torque efficiency and a high efficiency which extended over a great range of speed, that is, one which had a speed torque characteristic similar to that of the direct current series motor. The characteristic of an alternating current induction motor is that of a constant speed motor but by the introduction of a commutator almost any speed torque characteristic can be produced. It is evident, then, that we refer only to the commutator type; as the induction motor without commutator has not as yet been found suitable for traction work. In its general form the alternating current motor consists of one or more stationary electrical circuits magnetically related to one or more rotating electric circuits. These circuits may be excited by to one or more rotating electric circuits. These circuits may be excited by alternating current or some by alternating current and some by direct. Before taking up in general the theory of the single phase induction motor, it might be well to give the classes and types into which alternating current motors may be subdivided.
Citation: Coldwell, William Irving. The single phase railway. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Single Phase Railway; Railroad; Alternating Current Motor; Theses